2016
DOI: 10.20944/preprints201609.0046.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of Carbon Flux and Soil Moisture in Wetlands Applying Sentinel-1 Data

Abstract: Abstract:The objectives of the study were to determine the spatial rate of CO2 flux (Net Ecosystem Exchange) and soil moisture in a wetland ecosystem applying Sentinel-1 IW (Interferometric Wide) data of VH (Vertical Transmit/Horizontal Receive-cross polarization) and VV (Vertical Transmit/Vertical Receive-like polarization) polarization. In-situ measurements of carbon flux, soil moisture, and LAI (Leaf Area Index) were carried out over the Biebrza Wetland in north-eastern Poland. The impact of soil moisture a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Paloscia et al [36] developed an approach based on an artificial neural network to estimate soil moisture in nearly-real-time for Sentinel-1 data. Dabrowska-Zielinska et al [37] demonstrated the capability of Sentinel-1 data in estimating soil moisture and net ecosystem exchange in wetlands. These results are encouraging for the application of Sentinel-1A data to the estimation of soil moisture over grasslands.…”
Section: Introductionmentioning
confidence: 99%
“…Paloscia et al [36] developed an approach based on an artificial neural network to estimate soil moisture in nearly-real-time for Sentinel-1 data. Dabrowska-Zielinska et al [37] demonstrated the capability of Sentinel-1 data in estimating soil moisture and net ecosystem exchange in wetlands. These results are encouraging for the application of Sentinel-1A data to the estimation of soil moisture over grasslands.…”
Section: Introductionmentioning
confidence: 99%
“…In-situ measurement of soil moisture is considered as the most accurate method for drought monitoring but available for only small scales and limited areas [6]. Analyzes carried out by other researchers shows high relevance of using the spectral data for assessing the plants condition and biomass production [4,8,18]. The well-described indicator, NDVI was used in this work [5,22].…”
Section: Discussionmentioning
confidence: 99%
“…Research on the assessment of plants' condition and yield amount using NDVI was conducted in Poland by Dąbrowska-Zielińska [8], however, using spectral satellite data with a spatial resolution of 1 km. It cannot be clearly determined which environmental parameter effects in the best way on the plants condition represented by the NDVI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations